2022
DOI: 10.1021/acs.jpclett.2c02750
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Strong Synergy in the Interfacial Water Response of Binary Ionic and Nonionic Surfactant Mixtures

Abstract: Interfacial vibrational footprints of the binary mixture of sodium dodecyl sulfate (SDS) and hexaethylene glycol monododecyl ether (C12E6) were probed using heterodyne detected vibrational sum frequency generation (HDVSFG). Our results show that in the presence of C12E6 at CMC (70 μM) the effect of SDS on the orientation of interfacial water molecules is enhanced 10 times compared to just pure surfactants. The experimental results contest the traditional Langmuir adsorption model predictions. This is also evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Recent experimental and simulation studies have explored mixed micellization of amphiphilic block copolymers and ionic surfactants, specifically emphasizing pluronic-SDS systems. The mixed micellization of high MW pluronic F127-SDS and pluronic P123-SDS ,, have been thoroughly investigated using surface tension, electromotive force, light scattering, isothermal titration calorimetry, and SANS/SAXS analysis techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental and simulation studies have explored mixed micellization of amphiphilic block copolymers and ionic surfactants, specifically emphasizing pluronic-SDS systems. The mixed micellization of high MW pluronic F127-SDS and pluronic P123-SDS ,, have been thoroughly investigated using surface tension, electromotive force, light scattering, isothermal titration calorimetry, and SANS/SAXS analysis techniques.…”
Section: Introductionmentioning
confidence: 99%
“…HD-VSFG is a surface-specific technique that is capable of capturing vibrational features from molecular subgroups where the inversion symmetry is broken and the net dipolar contribution is non-zero. The details of the experimental setup specific to these experiments can be found elsewhere . We investigated solutions with SDS concentrations ranging from 10 to 100 μM and by varying the NaCl concentration from 0 mM to 1 M. For all studied SDS concentrations, we observe a highly nonlinear dependence of the water signal on the NaCl concentration detected with HD-VSFG, which indicates the occurrence of a two-dimensional (2D) hydrophobic collapse of the surfactant layer in a limited NaCl concentration range of 10–100 mM.…”
mentioning
confidence: 97%
“…The details of the experimental setup specific to these experiments can be found elsewhere. 25 We investigated solutions with SDS concentrations ranging from 10 to 100 μM and by varying the NaCl concentration from 0 mM to 1 M. For all studied SDS concentrations, we observe a highly nonlinear dependence of the water signal on the NaCl concentration detected with HD-VSFG, which Figure 1 shows HD-VSFG spectra of aqueous solutions containing 25 μM SDS and different NaCl concentrations ranging from 10 mM to 1 M. We performed the same NaCl concentration series experiments for 10, 25, 50, and 75 μM SDS solutions. The measured HD-VSFG spectra of those series can be found in SI 1.…”
mentioning
confidence: 99%
“…Recently, we studied binary mixtures of the anionic surfactant sodium dodecyl sulfate (SDS) and the nonionic hexaethylene glycol monododecyl ether (C 12 E 6 ). We found that the effect of SDS on the orientation of interfacial water molecules is multifold enhanced in the presence of C 12 E 6 at a critical micellar concentration (CMC) of 70 μM . Catanionic surfactant systems, which combine cationic and anionic surfactants, also show strong synergistic effects, resulting in a reduced CMC and enhanced surface activities, which in turn leads to large changes in solubility and degree of micellar aggregation .…”
mentioning
confidence: 99%
“…The addition of a nonionic surfactant like C 12 E 6 to a solution of SDS can also lead to an enhancement of the surface density of DS – . Obviously, a neutral surfactant does not screen the Coulomb repulsion between the DS – headgroups, which implies that the enhancement of the DS – surface density has a different origin.…”
mentioning
confidence: 99%